2020
DOI: 10.3390/jcm9072173
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lactobacillus acidophilus YT1 (MENOLACTO) on Improving Menopausal Symptoms: A Randomized, Double-Blinded, Placebo-Controlled Clinical Trial

Abstract: This study evaluated the efficacy of Lactobacillus acidophilus YT1 (MENOLACTO) for alleviating menopausal symptoms. This study was a multi-center, randomized, double-blinded, placebo-controlled clinical trial involving female subjects (ages: 40–60 years) with menopausal symptoms and a Kupperman index (KMI) score ≥ 20. Subjects were administered 1 × 108 CFU/day MENOLACTO or placebo, with the primary endpoint being total KMI score, and the effect of secondary endpoints on alleviating menopausal symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…In obese postmenopausal women, probiotics exert a protective effect by modulating the gut microbiota [ 44 , 45 ]. Lactococcus in the intestine is a genus of beneficial microbes which negatively associated with obesity [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In obese postmenopausal women, probiotics exert a protective effect by modulating the gut microbiota [ 44 , 45 ]. Lactococcus in the intestine is a genus of beneficial microbes which negatively associated with obesity [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…From these results, we would predict that Lactobacillus may be used to alleviate diseases related to menopause. A clinical trial in Korea reported that oral ingestion of lactobacilli by post-menopausal women improved symptoms related to menopause [ 47 ], but further studies are needed to investigate alleviation of menopause-related symptoms by administering Lactobacillus directly to the vagina rather than by oral administration to restore the vaginal microbiome to a pre-menopausal state.…”
Section: Discussionmentioning
confidence: 99%
“…See supplementary file to view comprehensive details for each included study. Eight studies evaluated the effects of probiotics on menopausal symptoms [21]; [22]; [23]; [24]; [25]; [26]; [27]; [28]. Fifteen studies explored probiotics and urogenital health including genitourinary syndrome of menopause [30]; [31]; [32]; ; [34]; [35], bacterial vaginosis [36], urinary tract infections [37]; [38], and vaginal atrophy [39]; [40]; [41]; [42]; [43]; [44]; [45].…”
Section: Study Characteristicsmentioning
confidence: 99%